Fleet vehicle dispatch and rebalancing method and simulation based on mobility-on-demand - Yang, Yifan (Nanyang Technological University, 2024)
With the blooming growth of urban populations and the consequent rise in passenger demand for efficient public transportation, MoD based transportation services, such as shared-public taxis and ride-hailing, have become crucial in urban mobility. However, these systems often face challenges like inefficient vehicle utilization, unmet passenger demand, and imbalance in vehicle distribution. In this dissertation, a series of novel methodologies for the dispatch and rebalancing of vehicle fleets are introduced, aimed at enhancing operational efficiency and customer satisfaction. By modelling the entire problem as an Integer Linear Programming problem with a set of constraints, the optimal decision set of vehicle rebalancing can be implemented into the rebalancing and dispatch system to refine the performance of the system. The simulation procedure is conducted on the real history taxi data of Beijing city, which contains key performance indicators such as average waiting time, service rate, and vehicle utilization rate. The results show that the effectiveness of proposed strategies is predictive and efficient. In the following works, the proposed models and strategies hold the potential to transform MoD services, making them more responsive, efficient, and sustainable, thereby enhancing the overall urban transportation landscape.